PERSEPSI MASYARAKAT TERHADAP PERAN KIAI DALAM PEMBERDAYAAN KEHIDUPAN BERAGAMA DI PURWOREJO, JAWA TENGAH (Public Perception on The Roles of Kiai in Empowering Religious Life in Purworejo, Central Java) - Sulaiman Sulaiman (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2016)
Kiai has been perceived as a respected figure and a model for society in which they  have important roles in empowering community. After the reformation era, in 1998,  the new situation has encouraged changes in many walks of life such as social, culture and politics of relationship between kiai and community. This paper aims to explore people’s perception on the roles of kiai in empowering religious life in Purworejo district, Central Java province. This study exercises a qualitative approach. The results show that there is positive perception of people toward the roles of kiai in empowering religious life. This is because most people followed Ahlus Sunnah wal Jamaa’ah school of thought, people are actively involved in religious gathering (majlis taklim), and they have experiences as santri (students) of pesantren (Islamic boarding school). On the other hand, few people mention that kiai have negative roles in empowering religious life, especially on enhancing people’s faith. This might be, because some people do not understand the concept of kiai, whereas other people appraise kiai objectively as a common person who has some weaknesses, therefore their behavior sometimes do not fit with the religious teaching.